Prevalence of Metabolic Syndrome in Japanese-Brazilians According to Specific Definitions for Ethnicity - Xavier, Natasha P. [UNESP]; Chaim, Rita C.; Gimeno, Suely G. A.; Ferreira, Sandra R. G.; Hirai, Amelia T.; Padovani, Carlos Roberto [UNESP]; Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP] (Mary Ann Liebert, Inc., 2010)
Background: The American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI), revising the National Cholesterol Evaluation Program for Adult Treatment Panel III (NCEP ATP III), and the International Diabetes Federation (IDF) have proposed definitions of metabolic syndrome that take into account waist circumference thresholds according to ethnicity. In this study we estimated the prevalence of metabolic syndrome in a Japanese-Brazilian population using NCEP definitions for Westerners (NCEPwe) and Asians (NCEPas), and IDF for Japanese (IDF).Methods: A total of 650 Japanese-Brazilians living in a developed Brazilian city and aged 30-88 years were included.Results: Metabolic syndrome prevalence according to NCEPwe, NCEPas, and IDF was, respectively, 46.5%, 56.5%, and 48.3%. Only 43.5% of subjects did not have metabolic syndrome by any of the 3 definitions, and 38.3% fulfilled metabolic syndrome criteria for all 3 definitions. Ten percent of subjects were positive for metabolic syndrome based on NCEPas and IDF, but not for NCEPwe. Because IDF requires abdominal obesity as a criterion, the frequency of subjects without metabolic syndrome according to IDF, but with metabolic syndrome by NCEPwe and NCEPas was 8.2%.Conclusions: Independent of the metabolic syndrome definition, Japanese-Brazilians present an elevated metabolic syndrome prevalence, which was higher when using NCEP criteria for Asians, followed by the IDF definition for Japanese.